Hearing the voices of tribals and adivasis - Chhungi, Hrangthan (Delhi ISPCK, 2014)
Papers presented at various consultations organised by the Commission on Tribals and Adivasis of the National Council of Churches in India held during 2009-2011.
section I. Indigenous peoples in India: tribal and adivasi -- section II. Crises encountered at different levels -- section III. Challenges for churches and institutions -- section IV. Challenges for praxis theologies.
"An NCCI centenary publication."
Keywords: Tribes; Indigenous peoples